Penanganan Rehabilitasi Medis dan Sosial dalam Strategi P4GN (Pencegahan dan Pemberantasan Penyalahgunaan dan Peredaran Gelap Narkotika) Berbasis Digital: Pendekatan Smart Power: Mewujudkan Masyarakat Bebas Narkotika - Seri Mughni Sulubara; Taifatul Jannah; Yeni Irma Normawati; Hilma Rahmatillah; Eka Lestari Sitepu; Riska Riska (Pusat Riset dan Inovasi Nasional, 2025)
Handling drug abuse is one of the main focuses in the Prevention and Eradication of Drug Abuse and Illicit Trafficking (P4GN) efforts in Indonesia. In this context, medical and social rehabilitation plays an important role as a recovery effort for addicts to return to optimal functioning in society. This community service activity uses a qualitative approach with a combination of observation, interview, and digital-based direct intervention methods in handling medical and social rehabilitation for drug abusers. This community service activity successfully implemented a digital-based medical and social rehabilitation strategy in supporting the P4GN program with a smart power approach. A web-based information system and mobile application designed to facilitate registration, monitoring, and mentoring of rehabilitation patients were successfully developed. This system provides easy access to information for the community and drug abusers to register and obtain rehabilitation services efficiently without having to come directly to the rehabilitation facility. The digital rehabilitation system is integrated with national electronic medical record platforms (such as SIRENA and the Ministry of Health's SATU SEHAT service), thus facilitating coordination between institutions and ensuring continuous monitoring of client health during and after the rehabilitation period. This community service activity successfully demonstrated that the handling of medical and social rehabilitation in a digital-based P4GN strategy with a smart power approach is an effective solution in an effort to realize a drug-free society. The smart power approach that integrates hard power (law enforcement) and soft power (prevention, community empowerment, and rehabilitation) with the support of digital information technology can improve the accessibility, effectiveness, and quality of rehabilitation services.